Analisis Pemanfaatan Digital Marketing, Brand Equity, Dan Brand Awareness Terhadap Keputusan Pembelian Produk Maternal Disaster Di Kota Malang - Saputra, Muhammad Shendy Tessario Yunas; Salim, Muhammad Agus; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted with the aim of finding out the influence of digital marketing, brand equity, and brand awareness on purchasing decisions for Maternal Disaster products in Malang City. This research uses a population of Malang City residents who have purchased Maternal Disaster products while the sample used in the research is Maternal Disaster consumers between the ages of 18-30 years in Malang City totaling 105 respondents. The methods used in this research are validity test, reliability test, normality test, classical assumption test, multiple linear regression test, hypothesis test, coefficient of determination test. The results of this research show that digital marketing has a negative effect on purchasing decisions, brand equity has a positive effect on purchasing decisions, brand awareness has a positive effect on purchasing decisions. Meanwhile, simultaneously it shows that digital marketing, brand equity, and brand awareness have a significant influence on purchasing decisions. Keywords: Digital Marketing, Brand Equity, Brand Awareness, Purchasing Decisions.